Development of a New Tool to Assess the Quality of Life of Patients with Hand–Foot Syndrome Receiving Capecitabine-Based Therapy: A Pilot Study - Jagdish, Prathepa; Kaur, Navdeep; Kapoor, Akhil; Mandavkar, Sarika; Ramaswamy, Anant; Ostwal, Vikas (South Asian Journal of Cancer, 2022)
Background Hand–foot syndrome (HFS) can result in significant deficits in health-related quality of life (HRQOL) and can lead to poor compliance, dose reduction, or interruption. This study was performed to assess the HRQOL with HFS on physical, psychological, social, and sexual aspects of patients receiving capecitabine-based chemotherapy with gastrointestinal cancer along with validating and assessing the reliability score of the questionnaire.Patients and Methods HFS-related QOL (HF-QOL) questionnaire was developed and validated in a sample of 30 patients randomly selected for this pilot study. The internal consistency of the tool was tested by calculating the Cronbach's α coefficient, while content and construct validity were assessed by Pearson's correlation. Statistical analyses were performed using SPSS version 25.0.Results Out of 30, 22 (73%) patients were males, mean age was 44 ± 13 years; 21 (70%) patients had grade 1 HFS, while 6 (20%) and 3 (10%) patients had grades 2 and 3 HFS, respectively. Cronbach's α coefficient was high for physical (0.79) and sexual scales (0.79), while it was moderately low for psychological (0.65) and social (0.53) domains. The average HF-QOL scores were 70.6 ± 13.2 in physical domain and 71.3 ± 23.7 in sexual domain indicating poor quality of life (QOL), while it was 50.9 ± 9.9 in social domain indicating moderately worse QOL. Grades 2 and 3 of HFS were found to have statistical significance on physical (0.0001), psychological (0.05), and social (0.02) domains, whereas sexual domain did not have any statistical significance (0.594).Conclusion This pilot study showed the feasibility of use and validity of a new patient-reported instrument, the HF-QOL, which measures the effect of HFS on daily activities (physical, psychological, social, and sexual domains) after capecitabine-based chemotherapy.
Keywords: hand–foot syndrome; quality of life; patient-reported outcomes; gastrointestinal cancer; capecitabine